An Analysis of Beach Debris Accumulation in Table Bay, Cape Town, South Africa - Swanepoel, Deborah (Department of Biological Sciences, 2018)
Two sites in Table Bay, South Africa, were examined for stranded debris between October and December 1994. One beach (Milnerton) is a popular recreation area in the metropolitan area whereas the other (Koeberg) is closed to public access. Daily and weekly accumulation rates were measured for both sites. A total of 40 041 items were collected, of which 81.7 % was plastic. Half of this was styrofoam. The majority of the debris was related to floating recreational litter, packaging material and polystyrene trays. Indications of increased inputs during the peak holiday season were recorded at the public beach (Milnerton). Locale was found to influence debris abundance and relative composition. Within-site variation was great, and longer sampling periods are necessary to overcome this variability. Daily and weekly sampling intervals were compared; weekly sampling yielded relatively lower totals and weights of articles than daily intervals. Total article weights were positively correlated to total article number. There were few foreign articles and articles supporting epiphytic marine organisms. Most persistent litter washed ashore, but appeared to derive from local, land-based sources. Daily accumulation rates were generally not correlated to weather conditions.